Unemployment and sectoral competitiveness in Southern European Union countries. Facts and policy implications - Dimian, Gina Cristina; Aceleanu, Mirela Ionela; Ileanu, Bogdan Vasile; Șerban, Andreea Claudia (Journal of Business Economics and Management, 2018)
This article addresses the problem of the main factors driving sectoral unemployment in the Mediterranean countries most affected by this phenomenon. The choice of the four countries (Greece, Italy, Spain and Portugal) relies on the fact that they are dealing with the highest unemployment rates in the European Union and a certain typology of the economic structure. The originality of our research is offered by its direction, less tackled until now, namely the focus on the particularities of the economic sectors, trying to capture differences between them. The importance and the impact of the results are supported by the methods used to produce them, indicators and econometric models that are on trend and bring extra information to available studies. Descriptive statistics and mismatch indexes are used to outline the economic and labour market structure, while the econometric models built on panel data capture the impact of factors such as GVA growth, specialization and labour market mismatches on the unemployment rate at six economic sectors level. Our paper makes three contributions to the literature. First, we have demonstrated that agriculture is the sector of activity less sensitive to output fluctuations in terms of unemployment and can become a buffer for the jobless in times of recessions. Second, we have proved that industry, as a whole, is highly responsive to economic developments and bad specialization could worsen unemployment situation in this sector. Third, we showed that educational mismatches have a significant impact on unemployment in those sectors of activity that employ low educated workforce.